Self-supporting electromagnetic shielding composite film and preparation method thereof

By using a combination of three-dimensional fractal silver dendrites and aramid nanofibers, a self-supporting electromagnetic shielding composite film was prepared, solving the problem of conductive filler selection and achieving high-efficiency electromagnetic shielding performance, which is suitable for flexible electronic components and circuits.

CN119432067APending Publication Date: 2025-02-14SUN YAT SEN UNIV
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411706200.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

In the existing technology, the selection of conductive fillers has problems such as low conductivity or poor chemical stability, which leads to insufficient electromagnetic shielding effectiveness of self-supporting electromagnetic shielding composite films, and the synthesis process is complicated and not suitable for large-scale use.

Method used

Three-dimensional fractal silver dendrites (AgFDs) were used as conductive fillers and mixed with aramid nanofibers (ANFs). A self-supporting electromagnetic shielding composite membrane was prepared by vacuum-assisted filtration technology to form a three-dimensional conductive network, thereby improving conductivity and electromagnetic shielding effectiveness.

Benefits of technology

Achieving high conductivity and electromagnetic shielding effectiveness in ultra-thin thicknesses, with conductivity ranging from 1.5×10⁴ to 2.0×10⁶ S/m and electromagnetic shielding effectiveness adjustable from 30 to 100 dB, it is particularly suitable for electromagnetic shielding of flexible electronic components and circuits.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a self-supporting electromagnetic shielding composite film and a preparation method thereof. The self-supporting electromagnetic shielding composite film is composed of three-dimensional fractal silver dendrites (AgFDs) and aramid nanofiber (ANFs). The preparation method comprises the following steps: carrying out suction filtration on AgFDs / ANFs mixed dispersion liquid by adopting a vacuum-assisted suction filtration technology to prepare a wet film, and then washing, drying and hot-pressing to prepare the composite film. Under the conditions that the mass fraction of AgFDs is 80-92 wt% and the total thickness is smaller than or equal to 20 microns, the conductivity of the composite film ranges from 1.5 * 10 < 4 > S / m to 2.0 * 10 < 6 > S / m, the electromagnetic shielding effectiveness can be adjusted within the range of 30-100 dB, the electromagnetic shielding effectiveness per unit thickness reaches up to 1500-6000 dB / mm, and the composite film is particularly suitable for electromagnetic shielding of flexible electronic components and circuits.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of electromagnetic shielding composite film material processing, and in particular, relates to a self-supporting electromagnetic shielding composite film and a preparation method thereof. Background Art

[0002] As electronic components and equipment develop towards high frequency, high speed and thinness, the problem of electromagnetic wave interference is becoming increasingly serious, and there is an urgent need to develop ultra-thin and high-efficiency electromagnetic shielding composite membranes. Self-supporting electromagnetic shielding composite membranes are favored because the finished product is in a solid state, and vacuum-assisted filtration technology has also become a commonly used method for manufacturing self-supporting electromagnetic shielding composite membranes. When using vacuum-assisted filtration technology to prepare self-supporting electromagnetic shielding composite membranes, nanocellulose (CNFs) or aramid nanofibers (ANFs) are generally selected as polymer matrices, among which ANFs are widely used due to their advantages of high mechanical strength and high stability. However, there are many problems in the selection of conductive fillers at present: the conductivity of the composite membrane filled with carbon-based materials is low, while the chemical stability of MXene is poor; although the conductive properties of the composite membrane are excellent when metal nanowires are used as conductive fillers, the synthesis process of metal nanowires is complicated and not suitable for large-scale use. In addition, when flaky silver powder is used as a conductive filler, the composite membrane is not easy to conduct electricity or there is a problem of too high a filling rate. Therefore, it is of great practical significance to screen suitable conductive fillers and mix them with ANFs to prepare ultra-thin and high-efficiency self-supporting electromagnetic shielding composite membranes. Summary of the invention

[0003] In view of the deficiencies in the prior art, an object of the present invention is to provide an ultra-thin self-supporting electromagnetic shielding composite film with high electromagnetic shielding effectiveness and a preparation method thereof.

[0004] In order to achieve the above object, the present invention adopts the following technical solutions:

[0005] A self-supporting electromagnetic shielding composite film is made of the following components in parts by weight: 80-92 parts of three-dimensional fractal silver dendrites (AgFDs) and 8-20 parts of aramid nanofibers (ANFs).

[0006] Preferably, in the above-mentioned self-supporting electromagnetic shielding composite film, the three-dimensional fractal silver dendrites refer to primary fractal structures with three-dimensional radiation and a size of 2 to 6 μm, and the tips of the secondary and tertiary fractal structures are silver powders with micro-nano structures.

[0007] Preferably, in the above-mentioned self-supporting electromagnetic shielding composite membrane, the preparation method of the aramid nanofiber is: stirring and peeling the aramid fiber in a mixed dispersion of potassium hydroxide (KOH), deionized water and dimethyl sulfoxide (DMSO) to form deprotonated nano-sized aramid fibers, and then adding deionized water under high-speed stirring conditions to obtain protonated aramid nanofibers (abbreviated as: aramid nanofibers, ANFs) with a wire diameter of 10 to 70 nm and a length of 10 μm.

[0008] Preferably, in the above-mentioned self-supporting electromagnetic shielding composite film, the preparation method of the self-supporting electromagnetic shielding composite film comprises the following steps:

[0009] The three-dimensional fractal silver dendrite dispersion and the aramid nanofiber dispersion are mixed to form a mixed dispersion, which is then filtered to prepare a wet film, and then washed, dried and hot-pressed to form a mixed dispersion.

[0010] Preferably, in the above-mentioned method for preparing the self-supporting electromagnetic shielding composite film, the method for preparing the self-supporting electromagnetic shielding composite film comprises the following steps:

[0011] (1) setting the molar ratio of silver nitrate to hydroxylamine solution, controlling the flow rate, and mixing the reaction solution at a constant rate using a syringe pump. After the reaction is completed, collecting the solid product, washing it with deionized water and ethanol for multiple times, and finally dispersing the three-dimensional fractal silver dendrites in DMSO with the assistance of polyvinyl pyrrolidone and ultrasound to prepare a three-dimensional fractal silver dendrite dispersion, referred to as AgFDs dispersion;

[0012] (2) Aramid fibers, DMSO, KOH and deionized water are mixed and stirred to obtain a deprotonated ANFs solution, and then an equal volume of deionized water is slowly added to the solution under high-speed stirring conditions to obtain a protonated aramid nanofiber dispersion, referred to as ANFs dispersion;

[0013] (3) The AgFDs obtained in step (1) and the ANFs dispersion obtained in step (2) are uniformly mixed to obtain an AgFDs / ANFs mixed dispersion, and the dispersion is then filtered, the wet film is washed with deionized water for multiple times and then placed in an oven to dry, and finally the dry film is hot-pressed to obtain a self-supporting electromagnetic shielding composite film.

[0014] Preferably, in the above-mentioned method for preparing the self-supporting electromagnetic shielding composite film, the molar ratio of the silver nitrate to the hydroxylamine solution in step (1) is 1:4 to 1:12, wherein AgNO 3The concentration is 0.4-0.8 mol / L, and the solution flow rate is set to 5-8 mL / min; the solid product is washed 3-5 times with deionized water and ethanol respectively; the mass concentration of the AgFDs dispersion is 0.5-2.0%; the molecular weight of the PVP is 5000-20000 g / mol, and the amount used is 0.5-1.0% of the mass of the AgFDs;

[0015] In step (2), the mass ratio of the aramid fiber, deionized water and DMSO is 0.50:10:540, 0.75:15:535, 1.00:15:535, 1.25:20:530 or 1.50:20:530, and the corresponding ANFs solution contents are 1.0, 1.5, 2.0, 2.5 and 3.0 mg / mL, respectively; the mixing and stirring time is 6 to 10 hours; the amount of KOH added is 1 to 2 times the mass of the aramid fiber; the speed of the high-speed stirring is set to 6000 to 10000 r / min, and the stirring time is 30 to 60 min; the amount of deionized water added is the same as the volume of the ANFs solution;

[0016] The filtration operation in step (3) is carried out on a sand core filtration device with an inner diameter of 40 mm, using a nylon filter membrane with a pore size of 0.22 μm. After the filtration is completed, the wet membrane is cleaned 3 to 5 times with deionized water; the drying temperature is set to 60 to 90°C, and the time is 12 to 24 hours; the temperature of the hot pressing is set to 110 to 130°C, the pressure is 20 to 30 MPa, and the time is 0.5 to 2.0 hours.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The self-supporting electromagnetic shielding composite film of the present invention uses three-dimensional fractal silver dendrites (AgFDs) as conductive fillers. AgFDs is a primary fractal structure that presents a three-dimensional radial shape, and the secondary and tertiary fractal structures have micro-nanoscale silver powder. In addition to having the same high conductivity and high stability as ordinary silver powder, the three-dimensional radial primary fractal structure helps to form a three-dimensional conductive network, reduce the percolation threshold of the composite film and improve the conductivity. In addition, AgFDs is prepared by reducing silver nitrate with hydroxylamine in an aqueous solution, which reacts quickly and completely, is easy to collect, and can be synthesized on a large scale. Using AgFDs as a conductive filler is scalable and reduces the cost of film production.

[0019] (2) Based on the basic principle of electrical conductivity, the present invention uses vacuum-assisted filtration technology to prepare a self-supporting electromagnetic shielding composite film, giving full play to the morphological advantages of three-dimensional micro-nanostructure fillers in constructing a highly conductive network. In the present invention, the electromagnetic shielding effectiveness of the composite film at a filling rate of 80wt% is already higher than 30dB, while the composite film filled with flaky silver powder using the same polymer matrix and film-making technology still does not show any conductivity at a filling rate of 92wt%. The technical and cost advantages of the present invention are obvious. The self-supporting electromagnetic shielding composite film obtained by the present invention has an electrical conductivity of 1.5×10 4 ~2.0×10 6 S / m, the electromagnetic shielding effectiveness is adjustable within 30 to 100dB, the electromagnetic shielding effectiveness per unit thickness is 1500 to 6000dB / mm, and the electromagnetic shielding performance is excellent. It is particularly suitable for electromagnetic shielding of flexible electronic components and circuits. DETAILED DESCRIPTION

[0020] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0021] The sources of the components in the following examples are as follows: Silver nitrate (AgNO 3 , ≥99.99%), hydroxylamine solution (NH 2 OH, 50% aqueous solution), polyvinylpyrrolidone (PVP, 10000 g / mol), dimethyl sulfoxide (DMSO, AR) and potassium hydroxide (KOH, AR) were purchased from Shanghai Aladdin Reagent Co., Ltd.; aramid fiber (K49) was purchased from DuPont; ordinary flake silver powder (AgF, average particle size 5 μm) was purchased from Northwest Institute of Rare Metal Materials, CNMC (Ningxia).

[0022] Embodiment 1:

[0023] This embodiment provides a self-supporting electromagnetic shielding composite film, and the preparation method thereof comprises the following steps:

[0024] (1) Set AgNO 3 With NH 2 The molar ratio of the OH solution is 1:6, AgNO 3 The concentration of the solution is 0.05 mol / L, NH 2The concentration of OH solution was 0.30 mol / L, the flow rate was set to 8 ml / min, and the reaction solution was mixed at a constant rate using a syringe pump. After the reaction was completed, the solid product was collected and washed three times with deionized water and ethanol, respectively. Finally, AgFDs was dispersed in DMSO with the assistance of PVP (1.0 wt% of the mass of AgFDs) and ultrasound to prepare a dispersion with an AgFDs content of 1.0 wt%.

[0025] (2) The magnetic stirring rate was set to 600 r / min, and the aramid fiber, KOH, deionized water and DMSO were mixed in a light-proof condition at a mass ratio of 0.75:1:15:535 for 8 h. During this process, the aramid fiber was dissolved by deprotonation to form a deprotonated ANFs solution with a content of 1.5 mg / mL. Then, the stirring rate of the high-speed disperser homogenizer was set to 8000 r / min, and an equal volume of deionized water was slowly added to the solution within 30 min to obtain an ANFs dispersion with a content of 0.75 mg / mL.

[0026] (3) 4.43 g of AgFDs dispersion and 15.91 g of ANFs dispersion were mixed evenly to obtain a AgFDs / ANFs mixed dispersion, and then the dispersion was filtered. The wet film was washed three times with deionized water, clamped with two PTFE plates, and placed in an oven to dry at 60 ° C for 24 h. Finally, the dry film was hot-pressed at 110 ° C and 25.0 MPa for 1 h to obtain a self-supporting electromagnetic shielding composite film with an AgFDs mass fraction of 80 wt%.

[0027] The total thickness of the self-supporting electromagnetic shielding composite film was tested to be 16 μm and the conductivity was 1.55×10 4 S / m, the electromagnetic shielding effectiveness in the X-band reaches 31.2dB, and the electromagnetic shielding effectiveness per unit thickness is 1950.0dB / mm.

[0028] Embodiment 2:

[0029] This embodiment provides a self-supporting electromagnetic shielding composite film, and the preparation method thereof comprises the following steps:

[0030] (1) Set AgNO 3 With NH 2 The molar ratio of the OH solution is 1:4, AgNO 3 The concentration of the solution is 0.06 mol / L, NH 2The concentration of OH solution was 0.24 mol / L, the flow rate was set to 5 ml / min, and the reaction solution was mixed at a constant rate using a syringe pump. After the reaction was completed, the solid product was collected and washed 5 times with deionized water and ethanol respectively, and finally, AgFDs was dispersed in DMSO with the assistance of PVP (0.75 wt% of the mass of AgFDs) and ultrasound to prepare a dispersion with an AgFDs content of 2.0 wt%.

[0031] (2) The magnetic stirring rate was set to 800 r / min, and the aramid fiber, KOH, deionized water and DMSO were mixed in a light-proof condition at a mass ratio of 1.00:1.5:15:535 for 6 h. During this process, the aramid fiber was dissolved by deprotonation to form a deprotonated ANFs solution with a content of 2.0 mg / mL. Then, the stirring rate of the high-speed disperser homogenizer was set to 8000 r / min, and an equal volume of deionized water was slowly added to the solution within 45 min to obtain an ANFs dispersion with a content of 1.0 mg / mL.

[0032] (3) 2.87 g of AgFDs dispersion and 10.05 g of ANFs dispersion were mixed evenly to obtain a AgFDs / ANFs mixed dispersion, and then the dispersion was filtered. The wet film was washed 5 times with deionized water, clamped with 2 PTFE plates, and placed in an oven to dry at 80 ° C for 12 h. Finally, the dry film was hot-pressed at 120 ° C and 30.0 MPa for 1 h to obtain a self-supporting electromagnetic shielding composite film with an AgFDs mass fraction of 86 wt%.

[0033] The total thickness of the self-supporting electromagnetic shielding composite film was tested to be 17 μm and the conductivity was 9.87×10 4 S / m, the electromagnetic shielding effectiveness in the X-band reaches 48.5dB, and the electromagnetic shielding effectiveness per unit thickness reaches 2852.9dB / mm.

[0034] Embodiment 3:

[0035] This embodiment provides a self-supporting electromagnetic shielding composite film, and the preparation method thereof comprises the following steps:

[0036] (1) Set AgNO 3 With NH 2 The molar ratio of the OH solution is 1:8, AgNO 3 The concentration of the solution is 0.06 mol / L, NH 2The concentration of OH solution was 0.48 mol / L, the flow rate was set to 6 ml / min, and the reaction solution was mixed at a constant rate using a syringe pump. After the reaction was completed, the solid product was collected and washed with deionized water and ethanol three times respectively, and finally, AgFDs was dispersed in DMSO with the assistance of PVP (0.5 wt% of the mass of AgFDs) and ultrasound to prepare a dispersion with an AgFDs content of 1.0 wt%.

[0037] (2) The magnetic stirring rate was set to 600 r / min, and the aramid fiber, KOH, deionized water and DMSO were mixed in a mass ratio of 1.50:2:20:530 for 10 h in a dark environment. During this process, the aramid fiber was dissolved by deprotonation to form a deprotonated ANFs solution with a content of 3.0 mg / mL. Then, the stirring rate of the high-speed disperser homogenizer was set to 10000 r / min, and an equal volume of deionized water was slowly added to the solution within 60 min to obtain an ANFs dispersion with a content of 1.5 mg / mL.

[0038] (3) 6.96 g of AgFDs dispersion and 5.52 g of ANFs dispersion were mixed evenly to obtain AgFDs / ANFs mixed dispersion, and then the dispersion was filtered. The wet film was washed three times with deionized water, clamped with two PTFE plates, and placed in an oven to dry at 70 ° C for 16 h. Finally, the dry film was hot-pressed at 130 ° C and 20.0 MPa for 1.5 h to obtain a self-supporting electromagnetic shielding composite film with an AgFDs mass fraction of 90 wt%.

[0039] The total thickness of the self-supporting electromagnetic shielding composite film was tested to be 18 μm and the conductivity was 7.24×10 5 S / m, the electromagnetic shielding effectiveness in the X-band reaches 71.0dB, and the electromagnetic shielding effectiveness per unit thickness is 3944.4dB / mm.

[0040] Embodiment 4:

[0041] This embodiment provides a self-supporting electromagnetic shielding composite film, and the preparation method thereof comprises the following steps:

[0042] (1) Set AgNO 3 With NH 2 The molar ratio of the OH solution is 1:4, AgNO 3 The concentration of the solution is 0.06 mol / L, NH 2The concentration of OH solution was 0.24 mol / L, the flow rate was set to 5 ml / min, and the reaction solution was mixed at a constant rate using a syringe pump. After the reaction was completed, the solid product was collected and washed 5 times with deionized water and ethanol respectively, and finally, AgFDs was dispersed in DMSO with the assistance of PVP (0.75 wt% of the mass of AgFDs) and ultrasound to prepare a dispersion with an AgFDs content of 2.0 wt%.

[0043] (2) The magnetic stirring rate was set to 800 r / min, and the aramid fiber, KOH, deionized water and DMSO were mixed in a light-proof condition at a mass ratio of 1.0:1:15:535 for 6 h. During this process, the aramid fiber was dissolved by deprotonation to form a deprotonated ANFs solution with a content of 2.0 mg / mL. Then, the stirring rate of the high-speed dispersing homogenizer was set to 8000 r / min, and an equal volume of deionized water was slowly added to the solution within 45 min to obtain an ANFs dispersion with a content of 1.0 mg / mL.

[0044] (3) 3.86 g of AgFDs dispersion and 7.21 g of ANFs dispersion were mixed evenly to obtain a AgFDs / ANFs mixed dispersion, and then the dispersion was filtered. The wet film was washed five times with deionized water, clamped with two PTFE plates, and placed in an oven to dry at 80 ° C for 16 h. Finally, the dry film was hot-pressed at 120 ° C and 25.0 MPa for 1.5 h to obtain a self-supporting electromagnetic shielding composite film with an AgFDs mass fraction of 92 wt%.

[0045] The total thickness of the self-supporting electromagnetic shielding composite film was tested to be 17 μm and the conductivity was 1.92×10 6 S / m, the electromagnetic shielding effectiveness in the X-band reaches 89.8dB, and the electromagnetic shielding effectiveness per unit thickness is 5282.4dB / mm.

[0046] Comparative Example 1

[0047] This embodiment provides a self-supporting electromagnetic shielding composite film using common flaky silver powder (AgF) as a conductive filler, and the preparation method thereof comprises the following steps:

[0048] (1) AgF was dispersed in DMSO with the aid of PVP (0.75 wt% of the AgF mass) and ultrasound to prepare a dispersion with an AgF content of 2.0 wt%.

[0049] (2) 3.86 g of AgF dispersion and 7.21 g of ANFs dispersion (1.0 mg / mL) were mixed evenly to obtain an AgF / ANFs mixed dispersion, and then the dispersion was filtered. The wet film was washed five times with deionized water, clamped with two PTFE plates, and placed in an oven to dry at 80°C for 16 h. Finally, the dry film was hot-pressed at 120°C and 25.0 MPa for 1.5 h to obtain a self-supporting electromagnetic shielding composite film with an AgF mass fraction of 92 wt%.

[0050] After testing, the total thickness of the self-supporting electromagnetic shielding composite film is 16μm, it is apparently non-conductive, the electromagnetic shielding effectiveness in the X-band reaches 12.2dB, and the electromagnetic shielding effectiveness per unit thickness is 762.5dB / mm.

Claims

1. A self-supporting electromagnetic shielding composite film, characterized in that The invention is prepared from the following components in parts by weight: 80 to 92 parts of three-dimensional fractal silver dendrites and 8 to 20 parts of aramid nanofibers.

2. The self-supporting electromagnetic shielding composite film according to claim 1, characterized in that: The three-dimensional fractal silver dendrites refer to silver powders with three-dimensional radiation of primary fractal structure and size of 2-6 μm, and micro-nanostructure at the tips of secondary and tertiary fractal structures.

3. The self-supporting electromagnetic shielding composite film according to claim 1, characterized in that: The preparation method of the aramid nanofiber is as follows: aramid fibers are stirred and peeled in a mixed dispersion of potassium hydroxide, deionized water and dimethyl sulfoxide to form deprotonated nanoscale aramid fibers, and then deionized water is added under high-speed stirring conditions to obtain protonated aramid nanofibers with a diameter of 10 to 70 nm and a length of 10 μm.

4. A method for preparing the self-supporting electromagnetic shielding composite film according to claim 1, characterized in that The steps include: The three-dimensional fractal silver dendrite dispersion and the aramid nanofiber dispersion are mixed to form a mixed dispersion, which is then filtered to prepare a wet film, and then washed, dried and hot-pressed to form a mixed dispersion.

5. The method for preparing the self-supporting electromagnetic shielding composite film according to claim 4, characterized in that The steps include: (1) setting the molar ratio of silver nitrate to hydroxylamine solution, controlling the flow rate, and mixing the reaction solution at a constant rate using a syringe pump. After the reaction is completed, collecting the solid product, washing it with deionized water and ethanol for multiple times, and finally dispersing the three-dimensional fractal silver dendrites in DMSO with the assistance of polyvinyl pyrrolidone and ultrasound to prepare a three-dimensional fractal silver dendrite dispersion, referred to as AgFDs dispersion; (2) Aramid fibers, DMSO, KOH and deionized water are mixed and stirred to obtain a deprotonated ANFs solution, and then an equal volume of deionized water is slowly added to the solution under high-speed stirring conditions to obtain a protonated aramid nanofiber dispersion, referred to as ANFs dispersion; (3) The AgFDs obtained in step (1) and the ANFs dispersion obtained in step (2) are uniformly mixed to obtain an AgFDs / ANFs mixed dispersion, and the dispersion is then filtered, the wet film is washed with deionized water for multiple times and then placed in an oven to dry, and finally the dry film is hot-pressed to obtain a self-supporting electromagnetic shielding composite film.

6. The method for preparing the self-supporting electromagnetic shielding composite film according to claim 5, characterized in that In step (1), the molar ratio of silver nitrate to hydroxylamine solution is 1:4-1:12, wherein the concentration of AgNO3 is 0.4-0.8 mol / L, and the flow rate of the solution is set to 5-8 mL / min; the solid product is washed 3-5 times with deionized water and ethanol respectively; the mass concentration of the AgFDs dispersion is 0.5-2.0%; the molecular weight of the PVP is 5000-20000 g / mol, and the amount used is 0.5-1.0% of the mass of the AgFDs; In step (2), the mass ratio of the aramid fiber, deionized water and DMSO is 0.50:10:540, 0.75:15:535, 1.00:15:535, 1.25:20:530 or 1.50:20:530, and the corresponding ANFs solution contents are 1.0, 1.5, 2.0, 2.5 and 3.0 mg / mL, respectively; the mixing and stirring time is 6 to 10 hours; the amount of KOH added is 1 to 2 times the mass of the aramid fiber; the speed of the high-speed stirring is set to 6000 to 10000 r / min, and the stirring time is 30 to 60 min; the amount of deionized water added is the same as the volume of the ANFs solution; The filtration operation in step (3) is carried out on a sand core filtration device with an inner diameter of 40 mm, using a nylon filter membrane with a pore size of 0.22 μm. After the filtration is completed, the wet membrane is cleaned 3 to 5 times with deionized water; the drying temperature is set to 60 to 90°C, and the time is 12 to 24 hours; the temperature of the hot pressing is set to 110 to 130°C, the pressure is 20 to 30 MPa, and the time is 0.5 to 2.0 hours.

7. The electromagnetic shielding effect of the self-supporting electromagnetic shielding composite film according to any one of claims 1 to 3 in flexible electronic components or circuits.

Citation Information

Patent Citations

  • Flexible electromagnetic shielding composite material and preparation method thereof

    CN111138836A

  • Flexible aramid nanofiber and silver nanowire composite electromagnetic shielding thin film material and preparation method thereof

    CN113999524A

  • High-thermal-conductivity electromagnetic shielding composite film and preparation method thereof

    CN118578746A

  • Dendritic silver-plated aramid electrically conductive filler and preparation method therefor and application thereof, and polymer / dendritic silver-plated aramid composite material

    WO2023082090A1